Highly sensitive differential Hexagonal Split Ring Resonator sensor for material characterization - Das, Gouree Shankar; Buragohai, Akash; Beria, Yatish; Al Gburi, Ahmed Jamal Abdullah; Kalita, Partha Protim; Doloi, Trishna (Elsevier B.V., 2023)
In this paper, a highly sensitive differential Hexagonal Split Ring Resonator (HSRR) sensor is presented operating at 5.3 GHz for permittivity characterization of organic liquids. The hexagonal design has a smaller surface area for better field concentration and also possesses a long lateral interaction length for better power transfer from the feed to the resonators. The sensor is designed by loading a 50Ω transmission line with a pair of symmetrically placed HSRRs on either side of the transmission line. Differential sensing is achieved by using one of the resonating elements as the reference and the other as the material sensing unit. The sensor is designed and fabricated on an FR4 substrate to keep the cost low without sacrificing sensitivity. The sensor’s performance is investigated using six Liquid Under Tests (LUTs), covering a wide range of dielectric constants (ε′ r) from 1 to 20.6, while two LUTs are taken as unknown samples, and their complex permittivity is accurately determined. Due to the high concentration of the electric field, the sensor delivers an extremely high normalized sensitivity of 4.646% (246.48MHz of average sensitivity). The sensor is capable of determining the complex permittivity of unknown LUTs with less than 1.15%error, with the additional advantage of differential sensing, thus making it immune to environmental fluctuations.